Worship as a Medium of Interfaith Dialogue - "A Missiological Perspective" - Ramli Sarimbangun (Eduvest - Journal of Universal Studies, 2024)
This paper aims to explore the role of worship as a medium for dialogue between religious communities, focusing on a missiological perspective. Highlighted issues include the lack of comprehensive understanding regarding the role of worship in promoting interfaith dialogue and the scarcity of research specifically linking worship with a missiological approach. This gap needs to be addressed. The research method used is a qualitative approach, conducting a comprehensive literature review on worship, interfaith dialogue, and missiology theory. The results of this study are expected to provide a better understanding of worship's role in facilitating interfaith dialogue. This research is also anticipated to contribute new insights to the field of missiology by exploring how worship can be a powerful tool for the church in fostering understanding and cooperation between different religious communities. The conclusion provides practical recommendations for church leaders, religious figures, and missiology practitioners to use worship as an effective medium for dialogue. By promoting interfaith dialogue through worship, it is hoped to strengthen tolerance, mutual understanding, and cooperation among religious communities, building harmony and peace in a pluralistic society. Ultimately, the goal is to create greater awareness of the importance of respecting religious differences and promoting cooperation through inclusive and dialogical worship practices.